(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2025)
The COVID-19 pandemic accelerated global digital transformation and reshaped the foundations of entrepreneurship. Businesses worldwide had to adapt rapidly to technological disruption, remote collaboration, and shifting consumer behaviour. This paper explores how digital entrepreneurship evolved within innovation ecosystems during and after the COVID-19 crisis (2020–2024). It identifies critical factors driving new venture creation, ecosystem resilience, and digital business model innovation. The research combines secondary data from 12 international reports and case studies of 50 startups across Europe and Asia. Findings reveal that post-pandemic ecosystems have transitioned toward hybrid innovation models combining digital scalability with local community engagement. The study concludes that sustainable recovery depends on policies that support digital literacy, open innovation, and inclusive access to technology.